Przejście z edukacji na zagraniczny rynek pracy młodych Polaków = The transition from education to foreign labour market of young Poles - Grabowska-Lusińska, Izabela (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The paper deals with the problems associated with entering into the labour market by graduates of various kinds of schools. However, it applies to a specific group of young Poles - migrants, who experienced professional initiation on foreign labour market. The article refers to the process of transition from education to foreign labour market, which is not related to a single act of undertaking work abroad, but to the period of entering into the foreign labour market, to the transition from one state on the labour market to another.
Keywords: migrations; self-development; gainful activity; labour market; subject perpetration; migracje; samorozwój; działalność zarobkowa; rynek pracy; sprawstwo podmiotowe